THE ROLE OF FATHERS IN STUDYING THE SOCIAL-PSYCHOLOGICAL ISSUES OF BOYS - Shoista Norbovayevna, Мuratova (PT. Antis International Publisher, 2025)
Objective: This article examines the role and responsibilities of fathers in shaping the social-psychological characteristics of boys. It highlights the critical importance of a father’s influence in the upbringing and development of their sons. Methods: The analysis is grounded in the evaluation of familial interactions and societal norms, focusing on how fathers contribute to fostering respect, discipline, and social adaptability in boys. Results: The findings reveal that boys raised in father-headed households are more likely to develop positive feelings of respect and admiration towards their fathers. Such relationships are instrumental in guiding boys to adhere to societal norms and avoid behaviors that could lead to social sanctions. Novelty: This study underscores the unique and indispensable role of fathers in preventing boys from engaging in norm-violating behaviors, thus ensuring their successful integration into society.